Asuhan Keperawatan pada Tn. R dengan Gangguan Sistem Pencernaan: Sirosis Hepatis di Ruang Dahlia RSUD dr. Soeselo, Kabupaten Tegal - Alma Thania Khusna; Esti Nur Janah; H.Wawan Hediyanto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Liver cirrhosis is a chronic disease characterized by progressive fibrosis, altered liver architecture, and the formation of regenerative nodules. Although it develops slowly, cirrhosis often leads to serious complications such as ascites, variceal bleeding, jaundice, and hepatic encephalopathy. According to the Global Burden of Disease Study 2019, cirrhosis is among the leading causes of death worldwide, with more than 1.4 million deaths annually. In Indonesia, the prevalence of cirrhosis is reported at 0.4% (Riskesdas, 2021) and shows an increasing trend over the years. This case study aims to describe the application of comprehensive nursing care in a patient diagnosed with liver cirrhosis using the nursing process approach. The research design was a case study conducted on Mr. R, who was admitted to Dahlia Ward at RSUD dr. Soeselo, Tegal. Data collection was carried out through interviews, observations, physical examinations, and medical record reviews. The results revealed that the main nursing problems identified were ineffective peripheral perfusion, ineffective breathing pattern, and knowledge deficit. Nursing interventions provided included positioning the patient in semi-fowler, monitoring vital signs, educating the patient about low-sodium diet and fluid restriction, and collaborating in the administration of diuretics and albumin. After three days of nursing care, the evaluation indicated clinical improvement, evidenced by reduced edema, decreased shortness of breath, and increased patient understanding of his disease and treatment plan. In conclusion, nursing care with a comprehensive process approach has a significant positive impact on the condition of patients with liver cirrhosis. Nurses play an essential role in assessment, planning, implementation, evaluation, and providing health education to prevent complications and improve patients’ quality of life.